Nieizsche/Zarathustra: subversion of autobiography - Marton, Scarlett (Estudios de Filosofía, 2003)
The purpose of this article, is to investigate the close ties between philosophical reflection and life experience in Nietzsche's mature work. Starting from a review of the criticism on the notion of subject, just as it appears in modernity, it shows that Nietzsche radically subverts the conception of intellectual autobiography, and thus, the idea of authorship.